EVALUASI PELAKSANAAN PROGRAM TERAPI AL-QUR’AN MELALUI MODEL CIPP DALAM MEMBENTUK SPIRITUAL ANAK BERKEBUTUHAN KHUSUS SPS ALAM ATIFA BOGOR - Tati Salmah Alawiah; Syarifah Gustiawati; Putri Ria Angelina (KOLONI, 2022)
The purpose of this study was to observe the implementation of the Al-Qur'an therapy program through an evaluation model of the Context, Input, Process, and Product aspects of the Al-Qur'an Therapy Program at SPS Alam Atifa Bogor. This study uses a qualitative approach in the field (field research). The object of this research is the implementation of the Qur'anic therapy program which is then reviewed through the CIPP evaluation model. The resource selection technique used a purposive sampling technique with the criteria of the resource person being able to answer the researcher's questions and in direct contact with the Qur'anic therapy process which involved nine resource persons consisting of the principal, four teachers, four guardians of students. Data collection techniques through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the research with the criteria of a relationship with Allah SWT, oneself, nature and others. In addition, it also shows that: 1) The background of the implementation is because students with special needs were found at SPS Alam Atifa Bogor, the objectives and curriculum (context aspects), 2) Criteria for organizers, criteria for teachers, participants, therapeutic methods and therapeutic media used in program implementation Al-Qur'an therapy (Input aspect), 3) Implementation of Al-Qur'an Therapy Program related to therapy schedule, teacher performance, student activities and evaluation (Process aspect), 4) Changes in therapy results in the form of good emotional control, formation of spirituality in children with special needs and the success of students in recognizing hijaiyyah letters and memorizing short suras (product aspect). Keyword: Al-Qur'an Therapy Program, Spirituality, Children with Special Needs, CIPP